Herpes Zoster: Clinical Manifestation, Treatment, and Prevention - Muhammad Izazi Hari Purwoko; Hari Darmawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Herpes zoster (HZ, shingles, zoster) is a disease due to reactivation and multiplication of persistent varicella zoster virus (VVZ) after suffering from previous varicella with characteristics of dermatomal rashes, pain, and unilateral. Dermatoms most often involved in HZ lesions are thoracal, trigeminal, lumbal, and cervical. The first lesion is usually erythematous macule or papule, which then turns into vesicle, then to pustule and to become crust, and persists for 2-3 weeks. The main goal of antiviral therapy in HZ patients is to reduce the expansion, duration, and severity of rashes and pain in primary dermatomes; prevent the spread of HZ to other places; and prevent post-herpes neuralgia. One of the prevention strategies for HZ in the elderly and high-risk individuals is vaccination using the varicella zoster virus vaccine that is live zoster vaccine or recombinant zoster vaccine.